2022
DOI: 10.3390/physiologia2030009
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Possible Effects of Wearing Exoskeletons during Welding on Heart Rate

Abstract: This study aims to investigate the possible effects of wearing exoskeletons during welding on heart rate. Additionally, the validity of a measuring instrument for determining acute heart rate is to be assessed. N = 15 young healthy subjects with welding experience took part in the study. The study design defines a one-hour workflow that abstracts welding and grinding tasks. The sequence is based on the internationally recognized standard DIN EN ISO 9606-1 and reproduces authentic work sequences in constrained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
2
3
0
Order By: Relevance
“…In general, we agree with Schalk et al ( 2022 ) that heart rate likely seems unsuitable to assess short-term effects of exoskeletons. However, Schalk et al ( 2022 ) found significant differences in the slope of the heart rate over a 30-min period. This suggests that investigations of physiological effects require long-term studies.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In general, we agree with Schalk et al ( 2022 ) that heart rate likely seems unsuitable to assess short-term effects of exoskeletons. However, Schalk et al ( 2022 ) found significant differences in the slope of the heart rate over a 30-min period. This suggests that investigations of physiological effects require long-term studies.…”
Section: Discussionsupporting
confidence: 91%
“…One participant experienced an increase in heart rate by almost 30% when wearing the exoskeleton, whereas for another person, heart rate decreased by more than 36%. Similar trends were observed by Schalk et al ( 2022 ), who attributed this to the body composition of the participants. Our data do not suggest a relationship between body composition and effects on heart rate.…”
Section: Discussionsupporting
confidence: 90%
“…As a result, his pelvis tilt angle increased. As for heart rates, existing studies showed that EXOs could reduce the heart rates of participants (e.g., [44,45]) or increase theirs (e.g., [46]). In this study, the wearing of EXOs increased the heart rates of the participants in Task 1, but the increase was not significant in Task 2.…”
Section: Discussionmentioning
confidence: 99%
“…This paper presented a pilot study for investigating workers' responses to the use of three passive EXOs (i.e., HeroWear Apex, Hilti EXO-01, and Ekso Evo) for two tasks: pushing/emptying gondolas and installing/removing wooden blocks in a construction workplace. The study quantitatively compared the difference in the workers' joint motions, As for heart rates, existing studies showed that EXOs could reduce the heart rates of participants (e.g., [44,45]) or increase theirs (e.g., [46]). In this study, the wearing of EXOs increased the heart rates of the participants in Task 1, but the increase was not significant in Task 2.…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of exoskeletons in reducing physical strain and fatigue among nurses has been a subject of investigation in several studies [ 5 , 8 , 17 , 18 ]. These wearable robotic devices are designed to provide mechanical support and assistance, aiming to alleviate the physical demands of nursing tasks and mitigate the risk of musculoskeletal injuries.…”
Section: Search Strategymentioning
confidence: 99%